Bridging theory and practice in port sustainability: a critical review of frameworks, technologies, and implementation strategies - Ahmad Shabib; Munjed A. Maraqa; Shahid Mustafa; Shitao Peng; Guoqiang Ma; Jianna Jia; Ning Qiu (International Journal of Sustainable Engineering)
Ports operations pose significant environmental, economic, and social challenges requiring comprehensive sustainability approaches. While the existing literature explores various aspects of port sustainability, reviews have typically focused on isolated dimensions or theoretical frameworks without substantial connection to real-world applications. Additionally, linkages between sustainability initiatives and the United Nations Sustainable Development Goals are primarily based on literature similarities rather than expert opinions and practical implementations. This study provides a state-of-the-art critical review of port sustainability, examining frameworks, technologies, and practical implementations. Through a systematic review of 67 studies from January 2014 to January 2024 across 30 countries, the research analysed environmental, economic, and social challenges, assessment methods, and implementation strategies. Key findings revealed a critical need for more integrated approaches addressing multiple sustainability dimensions simultaneously. Emerging technological solutions, including alternative energy sources and smart technologies, demonstrate promising results in practice. The review highlights successful sustainability initiatives from leading ports worldwide, providing valuable insights for enhancing sustainability practices elsewhere. The findings serve as a comprehensive guide for port authorities, policymakers, and researchers in developing sustainable strategies. The integration of theoretical frameworks with practical case studies offers a unique contribution to maritime sustainability literature and provides actionable recommendations for ports at various implementation stages.